Cardiac Sarcoidosis with a Rare Initial Manifestation: Sustained Monomorphic Ventricular Tachycardia - Dhadham, Gautamy Chitiki (Texas Heart Institute, 2011)
Sarcoidosis is a multisystem disease of unknown cause. Life-threatening complications or sudden death can occur when the disease involves the heart. Because cardiac sarcoidosis has diverse clinical presentations, its diagnosis can be a major challenge for clinicians. It is very rare for the initial manifestation of cardiac sarcoidosis to be sustained ventricular tachycardia, especially in a patient with no prior symptoms or history of the disease. Herein, we discuss the case of a 41-year-old black man who presented with nausea, vomiting, and palpitations on the day after he had consumed alcoholic beverages heavily. Electrocardiographic examination revealed sustained monomorphic ventricular tachycardia. An automatic implantable cardioverter-defibrillator corrected the patient's abnormal heart rhythm, and therapy with steroids and β-blockers resolved his symptoms. We describe the process that led to the diagnosis of cardiac sarcoidosis in this patient.